Transfusion-associated necrotizing enterocolitis (NEC) in extremely preterm infants: experience of a tertiary neonatal center in UK. (12th December 2022) - Stokes, Victoria; Rajai, Azita; Mukherjee, Devdeep; Mukherjee, Arindam
Abstract: Objective: To compare the characteristics and short-term outcomes in extremely preterm infants, who developed necrotizing enterocolitis (NEC) following a packed red blood cell transfusion (pRBC) within 48 h (TANEC), with those who developed NEC beyond 48 h (non-TANEC). Setting: A single-center retrospective cohort study in a Tertiary neonatal intensive care unit in the UK over a 5-year period Patients and methods: Extremely premature infants (23–27 weeks gestation) were selected. TANEC and non-TANEC incidence were calculated from the confirmed NEC group (defined as modified Bell's stage II and beyond). The characteristics and short-term outcomes of infants with TANEC in the first 8 weeks of life were compared to infants with non-TANEC. Results and interpretation: Incidence of confirmed NEC was 14% (28/207). On further subgroup analysis of the confirmed NEC cases, 46% (13/28) of infants were identified with TANEC and 54% (15/28) with non-TANEC. The incidence of TANEC did not correlate with the number of antecedent pRBC transfusions or the pre-transfusion median hemoglobin (Hb) levels. There were no significant differences in characteristics between the TANEC and non-TANEC groups. Infants within the TANEC group required more intensive neonatal care support, greater surgical intervention ( p -value 0.043) with loss of gut integrity and an increase in number of TPN dependency days ( p -value 0.014). Conclusions: A significantly worse clinical course and short-term outcome was observed in the TANEC group when compared with the non-TANEC group.